Approach to a multispecies VPA considering hake-anchovy trophic interactions in the north-western Mediterranean - Merella P.; Oliver P.; Alemany F.; Massutí E. (Dynamique des populations marines, 1998)
A methodology of Multispecies Virtual Population Analysis (MSVPA) for the Mediterranean fisheries has been developed. As an example, the impact of hake (Merluccius merluccius) predation on anchovy (Engraulis encrasicolus), two of the most important commercial species in north-western Mediterranean fisheries, has been analysed. The predator-prey relationships which exists between these species were described by two hypothetical predation matrices, derived from the current bibliography about biology, population dynamics and trophic ecology of both species. The results of the model showed that changes in the biomass of anchovy population, as well as in the economic values of landings of both species, could be obtained by varying the hake exploitation patterns. However, the variations predicted by the model must only be considered as a preliminary approach, as the figures which represent these changes do not take into account the interactions with other species, which could influence significantly the results of the analysis.
Deuxième Réunion du Groupe de Travail DYNPOP, 1996/10/02-05, Genova (Italy)